SIKAP DAN PERILAKU MEMBACA INFORMASI GIZI PADA LABEL PANGAN SERTA PEMILIHAN PANGAN KEMASAN - Qurrota A’yunil Huda; Dini Ririn Andrias (Media Gizi Indonesia, 2016)
Practicing healthy food pattern can prevent from degenerative disease. Nutrition label, including nutrition facts on food label can help people choosing healthier food. Attitude toward nutrition label can inﬂ uence nutrition label reading behavior and food choices, and reading food or nutrition label may inﬂ uence healthier food consumption. This study was aimed to ﬁ nd association between a  ttitude, nutrition label reading behavior and food choices among college students. This cross sectional study involved 98 undergraduate students class of 2013 Universitas Airlangga as the sample of the study. Respondents were made to answer 5 a  ttitude points and asked about their nutrition label reading behavior and food choices. Chi square and Pearson Chi square were used to analyze association between attitudes, nutrition facts reading behavior, and food choices. Students who had good   attitude about health and nutrition and nutrition label were not always became a label user or had healthy reason for food choices. Label users were not always had healthy reason for food choices. The study showed there was no association between attitudes and nutrition facts reading behavior, as well as between   attitude and food choices (p > 0,05). Further study to identify barriers of reading food and nutrition label behavior need to be conducted.